Glocal Insights to Neo-Carbon Energy and Its Forerunners - Merja Lang; Joni Karjalainen; Sirkka Heinonen (Finland Futures Research Centre, University of Turku, 2025)
This paper presents the results of an international survey on the forerunners of renewable energy. The survey was constructed in the Neo-Carbon Energy project, one of the strategic research openings of Tekes – the Finnish Funding Agency for Innovation. The foresight part of the project is conducted at Finland Futures Research Centre (FFRC). This survey explores the futures of an economy based on a new renewable energy based system in a peer-to-peer society 2050. The global meta-scenarios were reflected with a local and regional context in the survey to provide glocal insights. The results are used to modify and deepen the global meta-scenarios, and to contextualize them in different countries, particularly in the Neo-Carbon Energy project’s target countries: Kenya, Tanzania, South Africa, China, Korea and Australia. Respondents from USA, Latin America and Europe were also included.
The aim of the survey was to identify possible pioneers for each of the four transformational neo-carbon energy scenarios. Moreover, the possibility, probability and desirability of the scenarios was also evaluated by the respondents. The questionnaire addressed an international expert community of futurists, energy experts and entrepreneurs working on energy questions and societal change, which consists of members of the Club of Rome, the Millennium Project and national level energy and innovation networks. In total, the questionnaire was sent to 160 recipients in 14 countries. The response rate was 29 % with 39 respondents. Almost all respondents saw at least one of the scenarios possible in their local context, and the majority felt so about several scenarios. Value-Driven Techemoths 2050 scenario was seen as the most probable scenario, whereas Radical Startups 2050 and New Consciousness 2050, both based on deep ecology, were seen as the preferred scenarios.
Underlying these changes is a gradually growing consciousness of ecological threats. The spirit described in the Startups scenario can be found in other types of organisations: an entrepreneurial mind is needed also when starting a social experiment or a movement. As for aspiring startups, their radicality lies in the nature of the technology, in innovative business models, or their power in disrupting the market. With regard to Value-Driven Techemoths, some large companies are seen to have potential of turning into value-driven, but many also questioned their abilities. An analysis of the do-it-yourself mentality proved interesting: the “DIY” was seen as a mentality, activism, learning, a statement, business, fun, and even a necessity. Being a DIY energy entrepreneur or dealing with energy issues is not reserved for men only – East African respondents named entrepreneurs, of which several were women. Beyond engineering, in order to make their innovations spread, training is needed for other skills too: marketing, design thinking, accounting, and so forth. Ecological constraints are increasingly acknowledged by religious and spiritual movements. While this is beginning to push industrial change, for others this may imply adopting more traditional lifestyles.
Governmental support is crucial as an enabler: this includes soft measures (capacity-building, institutional support and networking), economic incentives or legal and regulatory measures. This means ending the dependence on coal, less regulation and taxation, and incentives that steer towards the production and consumption of renewables. While ideas or STI policies should not merely be replicated, for lessons learned it could be useful to look what those governments have done that already have combined cultural and societal strengths while enabling technological development. At a more simple stage, there are social practices in place in one country that are unknown elsewhere. Innovative business models linked to a technology, too, may at the moment only be in place in certain regions. Some respondents did discuss cross-sectoral linkages from renewable energy, such as solar and wind in linkage with the constructions and transport sector or mentioned novel energy services that are emerging from digitalisation. The use of solar energy in industry was mentioned in linkage with the mining sector. Across regions, “closed” grids were perceived to hold back the innovations by startup entrepreneurs, DIY engineers and large companies.
Pioneers nurture a sense of urgency for the change, and at the same time, they seem to realise that work and employment could in a growing degree emerge from renewable energy and digitalisation. If we want to see a neo-carbon future where decentralised and democratised energy prosumerism is a positive trend, support needs to be given to those pioneers who are identified as making that future – locally and regionally. Indeed, the survey findings could be used as material for outlining more concise and detailed regional strategies and for re-visiting economic or development visions. It could also be worth defining which innovations and social practices exactly have the highest potential of being radical or disruptive innovation to enable a truly transformative pathway to a solar and wind powered society. Only a few responses yet mentioned next generation technologies that support a 100% renewable energy system based on solar and wind. Therefore, this leaves considerable space for future innovation and competition to emerge in various niches.